Evaluation of Cellulolytic Enzyme Supplementation on Production Indices and Nutrient Utilization of Laying Hens Fed Soybean Hull Based Diets - Esonu, B.O.; Izukanne, R.O.; Inyang, O.A. (International Journal of Poultry Science, 2005)
A 120-day feeding trial was conducted to evaluate cellulolytic enzyme supplementation on production indices and nutrient utilization of laying hens fed soybean hull based diets. Seven experimental layers diets were formulated incorporating soybean hull meal at 0%, 10%, 20%, 30% (without enzyme supplementation) and 10, 20 and 30% (with 2.0% enzyme supplementation) dietary levels respectively. One hundred and forty seven (147), Shikka brown layers already 12 months in lay were divided into 7 groups of 21 birds each and randomly assigned to the 7 treatment diets in a completely randomized design (CRD). There were significant differences (P0.05) among the groups in body weight, egg yolk colour, shell thickness, albumen and yolk indices, horizontal and oblong circumferences and digestibility of dry matter and ash respectively. The group on 30% dietary level of soybean hull meal (without enzyme supplementation) performed significantly (P